BACES score: a predictor of health-related quality of life and associated factors in patients with nontuberculous mycobacterial pulmonary disease - Youngmok Park; Nakwon Kwak; Hyeontaek Hwang; Doosoo Jeon; Byung Woo Jhun; Kyung-Wook Jo; Young Ae Kang; Hyung-Jun Kim; Joong-Yub Kim; Young Ran Kim; Yong-Soo Kwon; Jae Ho Lee; et al. (Scientific Reports)
Abstract The evaluation of health-related quality of life (HRQOL) is gaining importance among patients with nontuberculous mycobacterial pulmonary disease (NTM-PD). We assessed whether the BACES score reflects HRQOL and associated factors in these patients. Data were collected from the nationwide NTM-KOREA prospective cohort of patients with NTM-PD who started antibiotic treatment and included symptoms, Quality of Life–Bronchiectasis (QOL-B) questionnaire, nutritional status using the Mini Nutritional Assessment–Short Form (MNA-SF) and Prognostic Nutritional Index (PNI), physical activity, body composition, spirometry, handgrip strength, and 6-min walking distance. Multivariate linear and logistic regressions were used for analysis. As the BACES score increased, so did the odds (adjusted odds ratio [95% confidence interval]) of cough (1.24 [1.04–1.48]), dyspnea (1.69 [1.28–2.27]), weight loss (1.78 [1.36–2.36]), and malnutrition, defined as MNA-SF score ≤ 7 (1.71 [1.21–2.45]), and PNI < 45 (2.14 [1.66–2.81]). The QOL-B respiratory symptom score (estimate: −2.259, P = 0.002) and 6-min walking distance (estimate: −18.015, P < 0.001) were negatively associated with the BACES score. Moreover, the odds of adipopenia (1.08 [1.03–1.13]), possible sarcopenia (1.80 [1.35–2.45]), and sarcopenia (2.09 [1.48–3.03]) increased in women. The BACES score can estimate HRQOL and associated conditions at antimicrobial treatment initiation in patients with NTM-PD.